"The Russian Revolution as ideal and practice. Failures, legacies and the future of revolution": Thomas Telios, Dieter Thomä y Ulrich Schmid (eds.) - Segovia, Juan Fernando (Derecho Público Iberoamericano, 2022)
Telios Thomas, Dieter Thomä & Ulrich Schmid (eds.), The Russian Revolution as ideal and practice. Failures, legacies and the future of revolution, Cham, Palgrave MacMillan, 2020 (e-book).